Lean synergy production model implementation in textile smes: a case study on efficiency and quality improvement - Toribio Alvarado, Brath Joseph (2024)
This research work focuses on small and medium-sized businesses (SMEs) in the textile sector, which are essential for the economy by generating employment and innovation. However, they face problems such as inefficiencies in production and difficulties in quality control. Although lean manufacturing methodologies have been applied to face these challenges, there is a lack of models specifically adapted to textile SMEs. The research seeks to close this gap by proposing a Synergistic Lean Production model that combines Change Management, 5S, Time and Method Measurement (MTM) and Line Balancing. The research question is: How can the integration of Lean methodologies improve operational efficiency and quality in textile SMEs? The objective is to develop a model that solves problems such as defects, long cycle times and low productivity, thus improving efficiency and quality in the operations of these companies. This study is relevant because it seeks to increase the competitiveness of textile SMEs by reducing costs and improving quality, fundamental aspects for their growth and sustainability in the global market. Furthermore, the research provides a validated model that enriches the academic literature on the implementation of Lean in SMEs. The methodological design included the pilot implementation of the model for six months, achieving significant improvements in productivity, reduction of defects and delivery times, demonstrating the effectiveness of the proposed approach to optimize production processes in textile SMEs.